2015
DOI: 10.1159/000439102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism and Prediction of Sorafenib Chemoresistance in Human Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer death worldwide, and prognosis remains unsatisfactory when the disease is diagnosed at an advanced stage. Many molecular targeted agents are being developed for the treatment of advanced HCC; however, the only promising drug to have been developed is sorafenib, which acts as a multi-kinase inhibitor. Unfortunately, a subgroup of HCC is resistant to sorafenib, and the majority of these HCC patients show disease progression even after an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 60 publications
1
73
0
1
Order By: Relevance
“…Thus, impairing the selfrenewal and stemness of CSCs is more effective for inhibition of tumor growth, as cancer stemness is the root of the tumorforming capacity. The treatment of hepatocellular carcinoma by conventional chemotherapy remains a therapeutic challenge, as hepatocellular carcinoma is a highly chemoresistant cancer and a subgroup of hepatocellular carcinoma is even resistant to molecular targeting agents such as sorafenib (39). Our observation that a low dose of PF-03084014 in combination with treatment with cis or dox can reach an inhibition rate of 80% to 90% in liver cancer spheres, indicating that targeting Notch can enhance chemosensitization of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, impairing the selfrenewal and stemness of CSCs is more effective for inhibition of tumor growth, as cancer stemness is the root of the tumorforming capacity. The treatment of hepatocellular carcinoma by conventional chemotherapy remains a therapeutic challenge, as hepatocellular carcinoma is a highly chemoresistant cancer and a subgroup of hepatocellular carcinoma is even resistant to molecular targeting agents such as sorafenib (39). Our observation that a low dose of PF-03084014 in combination with treatment with cis or dox can reach an inhibition rate of 80% to 90% in liver cancer spheres, indicating that targeting Notch can enhance chemosensitization of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…However, studies of HCC cell lines have revealed that it is not fully effective in preventing recurrence and progression because of resistance 14. Therefore, many research groups focus on the molecular mechanisms in sorafenib resistance in search of the established therapeutic agents that can overcome the resistance of HCC cells, and help develop potential strategies aimed at increasing its efficacy against HCC 15, 16.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a single miRNA targets multiple mRNAs, the alteration of multiple pathways attributed to the miRNA profile may act in concert and affect the sensitivity of HCC cells to sorafenib [8,9,10]. To date, several reports have suggested that miRNAs could influence the cellular response to drugs, and a profile of the miRNAs in peripheral blood could be biomarkers for the drug response of HCC [11,12,13]. However, the performance of miRNAs as biomarkers for the response to sorafenib treatment remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%